ZAWAHIR AL-TAQDIM WA AL-TA’KHIR FI SURAH AL-FATIHAH: DIRASAH BALAGIYYAH - Talqis Nurdianto (IAIN Surakarta, 2017)
The study of the introduction and delay of the basic detective in the science of Arabic rhetoric, it is one of the pillars on which the science of the meanings, because of the relevance of the purpose of the speaker, and the address and the place where the speech. Which are the meanings of the meaning of the meanings in the quest to develop controls that reach the meaning of speaking to the addresser intact? This research is based on the theory of eloquence about the introduction and delay and its methodology is a library research, and the Qur'anic text is the subject of it, namely Al-Fatihah And the stages in the analysis of the text passed by the researcher (1) comes the statement and search for the meaning of submission and delay when the Balaghein, including Abdul Qahir Jirjani and Sakkaki (2) submission and delay in interpreting the opening of the book when the interpreters, (3) Al-Fatiha has ten attributes, including five attributes of God Almighty, the Lord, the Merciful, the Merciful, the Owner, and five attributes of the slave, namely, slavery, seeking help, seeking guidance, seeking grace.